“La clef des vérités surnaturelles” : Simone Weil et l’esthétique - Negri, Federica (Scenari, 2021)
This contribution seeks to reinterpret the philosophy of Simone Weil (1909-1943) from an aesthetic-theological perspective, going beyond the stereotypes that often framed her thought in rigid and insufficient attributions, which risk to conceal the actual richness of the issues at stake and their heuristic power. In this way, Simone Weil’s proposal, which is placed at the center of a strong and unitary thought, with an absolutely unique style, appears to have no bearing on the sense of belonging to religious beliefs or philosophical doctrines, but rather it seeks for a way in this world. There is an existential coherence that leads her to combine Plato’s philosophy with materialism, renewed through mysticism, in order to save the “world of phenomena” from within, also thanks to the transformation made possible by beauty. On this path, both theoretical and practical, Simone Weil intertwines Gnostic tradition, Hinduism, Buddhism and Taoism in a very original way, always taking care to make them speak differently, in the name of their ability to detect the beauty of the world.